Does the application of anti-erosive substances on eroded dentin affect bond strength? : a systematic review = ¿La aplicación de sustancias antierosivas en dentina erosionada afecta la resistencia adhesiva? : una revisión sistemática - Costa, Moan Jéfter Fernandes
This systematic review evaluated whether using anti-erosive agents as a pretreatment of eroded dentin before bonding with resin composite affects the bond strength. A search was conducted by two reviewers in the PubMed, Embase, Scopus, Web of Science, and Science Direct databases in January 2023. Articles that employed artificially eroded human dentin and performed treatment prior to adhesion with anti-erosive substances were eligible. A validated tool with 12 items regarding in vitrostudies was used to assess the risk of bias in the selected articles, obtaining a final score for each study. Four in vitro studies were included in this systematic review. Most studies used the microtensile bond strength test; most failures were adhesive or mixed. No tested substance negatively affected the bond strength to eroded dentin. Sodium fluoride (NaF), tin-containing fluoride (Sn/F) and silver diamine fluoride (Ag(NH3)2F) have been proven not to interfere with or improve bond strength to eroded dentin